THU0391 Is there a Relationship between Hip Structural Analysis and Bone Mineral Density at the Hip and Spine?. (23rd January 2014) - Farrow, L.; Oldroyd, A.; Bukhari, M.
Abstract : Background: Hip structural analysis (HSA) has been suggested as possible method of improving prediction of hip fracture risk above that provided by current bone mineral density (BMD) use alone. To our knowledge no previous work has been conducted to determine the relationship between bone mineral density and hip structural analysis parameters in an unselected cohort in the hip and the spine (L1-L4). Knowledge of their association may well influence the utility of using both methods in clinical practice and possibly enable HSA to be used to predict risk of future fracture. Objectives: To decide if a link exists between BMD and hip structural analysis factors in the spine or hip. Methods: The analysis used data collected from patients attending for DEXA scan the Royal Lancaster Infirmary between 2004 and 2010. Hip structural analysis comprised a number of different measurements: Distance from centre of femoral head to centre of femoral neck (d1) and to inter-trochanteric line (d2); Mean femoral neck diameter (d3), distance from centre of mass of femoral neck to superior neck margin (y), hip axis length (HAL), cross-sectional moment of inertia (CSMI - theoretical measurement of femoral neck strength), shaft angle (A) neck/shaft angle (Θ) and proximal femur strength index (SI). Linear regression models were fitted using all the above parameters against both L1-L4 and Hip BMD. Separate models for males and females were also carried out as well as adjustment for the number of indications to scan. Results: 11155 patients' data (85% female) were analysed in the study, with a mean age of 63.8 years (SD=12.4) and a mean BMI of 26.8 kg/m 2 (SD=5.26). Regression data for each comparison are shown in table 1 . Values did not change significantly with individual analysis for males and females or when adjusted for number of indications for scan. Conclusions: CSA and to a lesser degree CSMI are important independent predictors of BMD, with CSA explaining over 60% of the variation in BMD at the hip and 38% at the spine. Use of CSA as a predictor of BMD has to our knowledge not previously been identified. Other HSA parameters were statistically, but not importantly, related to BMD; they may however still provide useful information regarding fracture risk. Use of CSA as a predictor of future fracture is warranted. Disclosure of Interest: None Declared